2023
DOI: 10.55905/cuadv15n2-043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flexural-tensile strength of high-performance soil-cement (HPSC) specimen bodies

Abstract: Current studies indicate that it is possible to obtain soil-cement products with similar performances to high performance concrete (HPC). In this context, this work aimed to evaluate the flexural rupture parameters of high-performance soil-cement specimens (HPSC) in relation to the cement percentage. Eighteen HPSC specimens were analyzed, produced with compaction moisture of 13% and pressure of 1.2 MPa. The average flexural-tensile strength of the specimens was 4.6 MPa with 30% cement, 5.6 MPa with 40% cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…It can be observed that, in general, the flexural strength values obtained at 28 days were always below 2.5 MPa. The only flexural strengths that exceeded 2.5 MPa were reported in the study by Rocha et al [23], achieving 5.8 MPa at 120 days, and those of Namboonruang et al [46,47], who obtained values <5.5 MPa at 28 days, albeit using a very high cement percentage (up to 50%). Therefore, even when using a high percentage of cement, the flexural strength values remained below 6 MPa at 28 days.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…It can be observed that, in general, the flexural strength values obtained at 28 days were always below 2.5 MPa. The only flexural strengths that exceeded 2.5 MPa were reported in the study by Rocha et al [23], achieving 5.8 MPa at 120 days, and those of Namboonruang et al [46,47], who obtained values <5.5 MPa at 28 days, albeit using a very high cement percentage (up to 50%). Therefore, even when using a high percentage of cement, the flexural strength values remained below 6 MPa at 28 days.…”
mentioning
confidence: 79%
“…In most of the soil-cement studies found, the cement percentage values are below 13%. Only in the studies by Rocha et al [23], Namboonruang [46,47], and Ademati et al [48] were higher cement percentages used. It can be observed that, in general, the flexural strength values obtained at 28 days were always below 2.5 MPa.…”
mentioning
confidence: 90%
See 3 more Smart Citations